2022
DOI: 10.3390/antiox11050895
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation during Puberty and Young Adulthood Mitigates Obesity-Induced Metabolic, Cellular and Epigenetic Alterations in Male Rat Physiology

Abstract: Selenium (Se) role in obesity is not clear. In addition, information on Se’s role in male physiology, specifically in obesity, is scarce. We conducted this study to evaluate the efficacy of Se supplementation, specifically during puberty until young adulthood, against obesity-induced deregulation of metabolic, cellular, and epigenetic parameters in epididymal fat and/or sperm cells in a rat model. High-fat-diet consumption by male rats during puberty and young adulthood significantly increased body weight, adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…One explanation would be the fact that the animals were lean and not submitted to any metabolic challenge. It has been highlighted that oxidative stress background could be a key interfering factor in selenium efficacy [ 146 ]. Thus, we [ 146 ] recently found that, when selenium was supplemented to obese fathers (a condition previously shown to program increased breast cancer risk [ 119 ]), during puberty and young adulthood, it led to amelioration of epididymal fat tissue obesity-induced oxidative stress and inflammation and reprogrammed sperm microRNA vital for spermatogenesis.…”
Section: Paternal Interventions With Bfcs As a Potential Epigenetic S...mentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation would be the fact that the animals were lean and not submitted to any metabolic challenge. It has been highlighted that oxidative stress background could be a key interfering factor in selenium efficacy [ 146 ]. Thus, we [ 146 ] recently found that, when selenium was supplemented to obese fathers (a condition previously shown to program increased breast cancer risk [ 119 ]), during puberty and young adulthood, it led to amelioration of epididymal fat tissue obesity-induced oxidative stress and inflammation and reprogrammed sperm microRNA vital for spermatogenesis.…”
Section: Paternal Interventions With Bfcs As a Potential Epigenetic S...mentioning
confidence: 99%
“…It has been highlighted that oxidative stress background could be a key interfering factor in selenium efficacy [ 146 ]. Thus, we [ 146 ] recently found that, when selenium was supplemented to obese fathers (a condition previously shown to program increased breast cancer risk [ 119 ]), during puberty and young adulthood, it led to amelioration of epididymal fat tissue obesity-induced oxidative stress and inflammation and reprogrammed sperm microRNA vital for spermatogenesis. This suggests that selenium supplementation during puberty and during these developmental stages could affect male physiology in the context of obesity, and it suggests that it could, potentially, positively affect offspring health [ 146 ].…”
Section: Paternal Interventions With Bfcs As a Potential Epigenetic S...mentioning
confidence: 99%
See 1 more Smart Citation
“…GPxs and TXNRDs are essential for correct β-cell function and insulin secretion; furthermore, Se regulates the transcription levels of the hypothalamic and GH/IGF axis-related genes responsible for growth promotion [ 1 ]. Apart from these endocrine actions, which affect lipid, protein and glucose homeostasis, Se modulates adipogenesis via GPx1 SREBP1, SelP and SelW, since this is a process where reactive oxygen species (ROS) are used as transmitters [ 2 , 3 ]. These effects are even more important during intense growth periods, such as gestation, lactation, adolescent and embryogenic periods, where tissues are growing and in some cases developing [ 1 , 2 ].…”
mentioning
confidence: 99%
“…Apart from these endocrine actions, which affect lipid, protein and glucose homeostasis, Se modulates adipogenesis via GPx1 SREBP1, SelP and SelW, since this is a process where reactive oxygen species (ROS) are used as transmitters [ 2 , 3 ]. These effects are even more important during intense growth periods, such as gestation, lactation, adolescent and embryogenic periods, where tissues are growing and in some cases developing [ 1 , 2 ].…”
mentioning
confidence: 99%